ANALYSIS OF MSL TG-13 PRESSURE GAUGE CALIBRATION METHOD - Adindra Vickar Ega; R. Rudi Anggoro Samodro (Instrumentasi, 2014)
Analysis of MSL TG-13 method by performing calibration of a 0.6% class-ranged 4,000 kPa pressure gauge had been conducted. The calibration was done by using a 0.1% class-ranged 40 bar test gauge as a standard. The purpose of the analysis was to verify the MSL TG-13 method with the widely used standard method Deutscher Kalibrierdienst (DKD-R 6-1). Parameters for the analysis were Error number (En) for the degree of equivalence of both methods, maximum error value according to the requirement in reference document BS en 837-1:1988 for each accuracy class. The result showed that MSL TG-13 method was consistent and complying with the widely used standard methods DKD-R 6-1, proven by En values ≤ 1 in each pressure point. The maximum error of pressure gauge, by using both methods, also complied with the requirement stated in BS En 837-1:1998, which was less than ± 0.6%. Therefore, MSL TG-13 method had been analyzed and could be implemented for pressure gauge calibration.